2016
DOI: 10.1093/jxb/erw279
|View full text |Cite
|
Sign up to set email alerts
|

Cold acclimation is accompanied by complex responses of glycosylphosphatidylinositol (GPI)-anchored proteins in Arabidopsis

Abstract: HighlightChanges in GPI-anchored proteins in plasma membrane-, microdomain-, and apoplast-fractions suggest the involvement of GPI-anchored proteins in the acquisition of freezing tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 67 publications
2
44
2
Order By: Relevance
“…Roots of Pisum sativum grown under clinorotation also show shifts in membrane composition in sterol-enriched membrane domains known as "lipid rafts" (Kordyum et al, 2018). Membrane-bound GPI-APs, such as SKU5, localize to these lipid raft nanodomains and are important to stress acclimation, including spaceflightassociated stress (Minami et al, 2008;Mazars et al, 2014;Ferl et al, 2015;Takahashi et al, 2016Takahashi et al, , 2019Yeats et al, 2018). ABA signaling proteins also localize to these membrane domains in a sterol-dependent manner (Demir et al, 2013).…”
Section: Sku5 Mutation Produces a Dramatic Increase In Differential Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Roots of Pisum sativum grown under clinorotation also show shifts in membrane composition in sterol-enriched membrane domains known as "lipid rafts" (Kordyum et al, 2018). Membrane-bound GPI-APs, such as SKU5, localize to these lipid raft nanodomains and are important to stress acclimation, including spaceflightassociated stress (Minami et al, 2008;Mazars et al, 2014;Ferl et al, 2015;Takahashi et al, 2016Takahashi et al, , 2019Yeats et al, 2018). ABA signaling proteins also localize to these membrane domains in a sterol-dependent manner (Demir et al, 2013).…”
Section: Sku5 Mutation Produces a Dramatic Increase In Differential Gmentioning
confidence: 99%
“…SKU5 is a glycosylphosphatidylinositol-anchored protein (GPI-AP), and as such is a component of discrete plasma membrane nanodomains known as "lipid rafts" (Borner et al, 2005;Elortza et al, 2006;Chen et al, 2018;Mamode Cassim et al, 2019). These nanodomains of the plasma membrane and their associated GPI-APs play roles in stress response signaling at the interface between the cell wall and membrane, where they are envisioned to help shape the "signatures" that activate downstream plant adaptive responses to the stresses they experience (Minami et al, 2008;Takahashi et al, 2013Takahashi et al, , 2016Takahashi et al, , 2019Shabala et al, 2015;Yeats et al, 2018;Miki et al, 2019). The endocytosis of SKU5 and other GPI-APs is modulated across the root tip by salt and auxin treatments, linking the movement of these proteins to stress responses (Baral et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additional differences could exist in the regulation of these genes during the diurnal cycle or in response to environmental factors. Some GPI-anchored proteins appear to be released to the apoplast (Takahashi et al, 2016), and this seems to be the case for a fraction of BGLC3 activity in 35S:BGLC3 lines (Fig. 4C).…”
Section: The Roles Of Xyloglucan B-glucosidasesmentioning
confidence: 83%
“…More recently, BGLC3 has been identified in a membrane fraction enriched in GPI-anchored proteins through phospholipase digestion (Takahashi et al, 2016). That study also analyzed an apoplastic fraction, where it identified BGLC1 but not BGLC3.…”
Section: Discussionmentioning
confidence: 94%
“…AtFLA3-silenced Arabidopsis had abnormal pollen grains, also suggesting a function in pollen formation [24]. FLAs have also been implicated in cell-cell communication [13], shoot development [25,26], seed mucilage adherence [27], glycan stabilization [28] and in response to stresses from salt [29][30][31], cold [32] and hydrogen peroxide [33].…”
Section: Overexpression Of Ghgalt1 Promoted Cotton Fiber Development mentioning
confidence: 99%